Quantum-dot color conversion film patterned by screen printing and overprinting process for display backlights. (January 2022) - Huang, Bingle; Chen, Enguo; Sun, Lei; Guo, Tailiang
Highlight: An effective preparation method is proposed for patterning quantum-dot color conversion film (QDCCF). The QD sub-pixel arrays can be precisely fabricated by two rounds of screen printing. An efficient white-balance adjusting method is successfully applied for patterned QDCCF. The target D65 color characteristics are well satisfied from the prepared backlight sample. The color gamut can reach the color gamut can reach 86.1% Rec. 2020 in CIE 1976 chromaticity diagram from our method. Abstract: The paper presents an effective preparation approach for patterning quantum-dot color conversion films (QDCCF) in white-balance display backlights, where the red and green sub-pixel arrays are respectively fabricated by precise screen printing technology and the subsequent overprinting process. By using the D65 light source as a design target, a theoretical adjustment method for output white balance is proposed, in which the quantity ratio of QDs can be obtained by combining the theoretical balance of three primary colors, the experimental balance of the QD's intensity, and the transmittance of color filter (CF). The ratio of green/red QDs for the target white balance was verified by both the experiment and theoretical calculation. Results show that the measured chromaticity coordinates of the backlight sample are (0.3138, 0.3402), the corresponding color temperature is 6385 K, and the color gamut can reach 86.1% Rec. 2020 in CIE 1976 chromaticity diagram. The experimental results accords well with the design theory, which supports that this method could be an alternative way for the fabrication of QDCCF.